Factors that Influence the Coverage of Vaccination against Pneumococcal Infections of Children up to 1 Year Old of Age at the Starting Phase of Vaccination - N. N. Filatov; M. P. Kostinov; T. N. Elagina; M. N. Loktionova; E. V. Lisitsyna; Y. B. Novikova (Эпидемиология и вакцинопрофилактика, 2017)
Whereas the quality of the program depends on promptness, full coverage, vaccination schedule abidance. Taking new Moscow regions as an example there have been studied factors influencing vaccination against Pneumococcal infection (PI). Insufficient provision of the vaccine to reach the desired level of coverage has been detected: in 2014 only 67.57% of liable children could receive double vaccination; the available quantity of vaccine in 2015 was able to provide 33. 84% of children up to 12 months old with double vaccination.However, the actual number of children vaccinated turned to be much lower (0.23% in 2014 and 20.85% in 2015).The survey of the doctors with the purpose of defining the level of knowledge and commitment to the vaccination against PI has shown a modest level of epidemiology, clinical implications, PIimmunoprophylaxis method awareness. Parental attitude towards PI vaccination has been estimated as positive. Parental interest to opportunities of immunoprophylaxis against PI is worthwhile noting despite the insufficient level of knowledgeability of its effects. Hence 74.5% of parents whose children are not vaccinated against PI would like to start vaccination, however a part of them look into receiving more information (29.41% parents).